SMAD3 deﬁciency promotes inﬂammatory aortic aneurysms in angiotensin II–infused mice via activation of iNOS - Tan, Eddie H. (2013)
Ninety percent of the patients carrying distinct SMAD3 mutations develop aortic aneurysms and dissections, called aneurysms-osteoarthritis syndrome (AOS). However, the etiology and molecular events downstream of SMAD3 leading to the pathogenesis of aortic aneurysms in these patients still remain elusive. Therefore, we aimed to investigate the vascular phenotypes of SMAD3-knockout mice. Methods and Results‒We showed that angiotensin II-induced vascular inflammation, but not hypertension, leads to aortic aneurysms and dissections, ultimately causing aortic rupture and death in these mice. Lipopolysaccharide-triggered inflammation confirmed that enhanced aortic macrophage recruitment was essential for aneurysm formation in angiotensin II-infused SMAD3-knockout mice. In contrast, phenylephrine-triggered hypertension alone was insufficient to induce aortic aneurysms in these mice. Using uniaxial tensile and contractility tests, we showed that SMAD3 deficiency resulted in defective aortic biomechanics and physiological functions, which caused weakening of the aortic wall and predisposed these mice to aortic aneurysms. Chromatin immunoprecipitation (ChIP) and re-ChIP assays revealed that the underlying mechanism involved an aberrant upregulation of inducible nitric oxide synthase (iNOS)-derived nitric oxide production and an activation of elastolytic matrix metalloproteinases 2 and 9. Administration of clodronate-liposomes and iNOS inhibitor completely abrogated these aortic conditions, thereby identifying iNOS-mediated nitric oxide secretion from macrophages as the downstream event of SMAD3 that drives this severe pathology. Conclusions‒Macrophage depletion and iNOS antagonism represent two promising approaches for preventing aortic aneurysms related to SMAD3 mutations and merit further investigation as adjunctive strategies for the life-threatening manifestations of AOS.